Utilization of Land Pawning in Customary Law and Its Solutions Under Islamic Law - Imron Rosyadi; Rizka Rizka (Jurnal Jurisprudence, 2021)
Purpose: This research aims to ascertain the practice of land pawning as security for loans and understand its law. A land pawner utilizes the collateral and retains the proceeds. However, a land pawnbroker is not entitled to obtain the pawner’s land management results.Methodology: This study belongs to normative juridical research, examining the relevant legal provisions and their implementation in society. This research investigated problem-solving in the practice of land pawning under customary law.Findings: The findings reveal that the customary pawning practice refers to the pawner’s land position as collateral. Muslim communities sometimes commit land pawning to obtain loans. The land pawner utilizes the collateral and retains the proceeds. In contrast, the land pawnbroker receives no benefit from the pawner’s land management.Practicality: This study is anticipated to guide pawnshops and banking institutions to ensure that solutions that conform to Islamic law are developed when pawning land following customary law. Islamic law offers a solution to employ a multi-contract, not a single one, as conducted so far, among others via qard and ijarah contracts.Novelty/Originality: The solution to the land pawning issue is utilizing a multi-contract, such as qard and ijarah contracts. An ijarah contract is not a condition or ta’aluq of the qard contract, as is the case with customary law’s practice of pawning. The ijarah agreement is entered into when pawned commodities are used as a means out of the deadlock created by the practice of land pawning contracts according to customary law, which utilizes a single contract. The profit earned by the pawner is derived from ijarah. Both parties gain equally in this case; the owner of the pawned property retains ownership of the lien and receives a profit share from the rent on the land used as collateral for his obligations.